2016
DOI: 10.4103/0366-6999.179803
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Therapy Regimen for Helicobacter Pylori Eradication

Abstract: Objective:Helicobacter pylori (H. pylori) eradication remains a challenge with increasing antibiotic resistance. Hybrid therapy has attracted widespread attention because of initial report with good efficacy and safety. However, many issues on hybrid therapy are still unclear such as the eradication efficacy, safety, compliance, influencing factors, correlation with antibiotic resistance, and comparison with other regimens. Therefore, a comprehensive review on the evidence of hybrid therapy for H. pylori infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
1
10
0
3
Order By: Relevance
“…In one review article, a total of 1871 patients in 12 studies received hybrid therapy[ 26 ]. The eradication rate of H. pylori was 82.6%-99.1%, and pooled analysis showed the eradication rate was 91.2% in per-protocol analyses.…”
Section: Discussionmentioning
confidence: 99%
“…In one review article, a total of 1871 patients in 12 studies received hybrid therapy[ 26 ]. The eradication rate of H. pylori was 82.6%-99.1%, and pooled analysis showed the eradication rate was 91.2% in per-protocol analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Hybrid regimens are another type that proved their efficacy in a recent meta-analysis [143]. In 2 recently published Greek studies, an over 90% eradication rate in per-protocol analysis was proved [129,142].…”
Section: Recommendation Grade: A; Evidence Level: 1b; Agreement Levelmentioning
confidence: 99%
“…A prospective study this year of hybrid therapy as a first‐line regimen was disappointing, revealing an eradication rate of 77% . A systematic review published this year reported 77%‐97% eradication with hybrid therapy and excellent compliance with low adverse event rates …”
Section: Sequential Concomitant and Hybrid Therapymentioning
confidence: 99%
“…33 A systematic review published this year reported 77%-97% eradication with hybrid therapy and excellent compliance with low adverse event rates. 34 A head-to-head trial of hybrid vs concomitant therapy was carried out in Iran which demonstrated eradication rates of 87.3% for hybrid therapy compared to 80.9% for sequential. 35 One systematic review of 12 trials comparing sequential, concomitant and hybrid therapies showed no significant difference in eradication rates between the treatments with similarly high compliance rates and acceptable adverse event rates.…”
Section: Sequential Concomitant and Hybrid Therapymentioning
confidence: 99%